Definitive IMRT for Stage III Thymic Carcinoma: A Brief Report and Literature Review - Dooley, Sarah A.; Anderson, Carryn M. (Frontiers in Oncology, 2016)
Introduction Thymic carcinoma is a rare malignancy often presenting at an advanced stage. Radiosurgery and chemotherapy are often the only treatment options available to physicians. Methods A 70-year old man presented with an unresectable Stage III thymic tumor and was treated with 45Gy in 12 fractions followed by a boost of 21.6 Gy in 12 fractions. He was also treated with bortezomib for multiple myeloma unrelated to his primary malignancy. Results The patient made a full recovery following the radiation regimen and remained disease free four years after treatment Conclusion Exclusive treatment with IMRT provides a viable treatment option for patients presenting with advanced stage thymic carcinoma.